Nil per os in the management of oropharyngeal dysphagia—exploring the unintended consequences - Cimoli, Michelle; Gibney, Jennifer; Lim, Mathew; Castles, Jo; Dammert, Pedro (Frontiers in Rehabilitation Sciences, 2024)
Nil per os (NPO), also referred to as Nil by Mouth (NBM), is a health-related intervention of withholding food and fluids. When implemented in the context of a person with dysphagia, NPO aims to mitigate risks of aspiration. However, evidence demonstrating that NPO is beneficial as an intervention for people with dysphagia is lacking. This paper explores the theoretical and empirical evidence relating to the potential benefits and adverse effects of NPO and asserts that NPO is not a benign intervention. This paper argues for applying an ethics framework when making decisions relating to the use of NPO as an intervention for dysphagia, in particular addressing informed consent and a person's right to self-determination.